Metamorphosis of Social and Environmental Accounting: Constructing Sustainability Accounting with Spirituality Dimension - Sukoharsono, Eko Ganis (Accounting Department,, 2010)
AbstractThe purpose of this paper is to examine the metamorphosis of social and environmental accounting into sustainability accounting. Postmodernism perspective is used to construct Sustainability Accounting with Spirituality Dimension, using the framework of James Cameron (2009) with his Avatar. Avatar as a work of postmodernism has stunned the world with its materialistic understanding (represented by â€œthe skyâ€ with the command of Colonel Miles Quaritch) and inhabitants of Pandora (with its beauty of social, environmental, spiritual life). Postmodernism in Avatar is able to foster the spirit of spirituality and transcendental spirit of nature and environment.By using the Avatar postmodernism metaphor, the paper concludes that sustainability accounting with spiritual dimension as a metamorphosis of social and environmental accounting could be used to report organizational activities. Principly, accounting events cannot be separated only with the economic dimension, but social, environmental dimensions, and even spiritual turned are also present at the organizationâ€™s event. The paper also argues that an organizational performance which has been dominated only by the measuring instruments of calculation of numbers and monetary figures will only make it â€œfrozenâ€. Narrative, expressive, as well as contextual, are all equally to take an important part in the expansion of an organizational performance of reporting. If it is only an economic dimension, the organizational performance would be â€œdryâ€. The expansion to build the social, environmental, and spiritual dimension is a new generation of models in a way to express the organizationâ€™s events. All of these can be presented in the sustainability accounting reporting system with a spiritual dimension.